PERAN TR.ANSFORMASIONAL LSM BAGI PEMBELAJARAN POLITIK RAKYAT - ROHMAN, ARIF (Universitas Negeri Yogyakarta, 2005)
Economic policies that spoil only big conglomerates and foreign capitalist and political policies that continously restrict and ignore democratic values and human rights have made lay people and civil power weak Therefore. Non-Government Organizations (NGO) as voluntary organizations, especially in 1990s, tried to enpower the civil people in order to be able to face the government. NGOs made such an attempt to achieve tha aspiratiron of making a civil society into reality, the society is not natural society or political society anymore, but a society in the highest level, namely civil society. It is a society whose members have an independent atlitude, an ability to develop the self, and an ability to restrict the government intervention in the reoliy that they have created as the space of their own activities.